2011
DOI: 10.1007/s10096-011-1196-z
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcome of HIV-infected patients admitted to the intensive care unit

Abstract: The purpose of this investigation was to analyse the impact of the availability of highly active antiretroviral therapy (HAART) on the long-term outcome of human immunodeficiency virus (HIV)-infected patients admitted to the intensive care unit (ICU). A retrospective cohort study of HIV-infected patients admitted to the ICU was undertaken. Outcomes in the pre-HAART era (1990-June 1996), early- (July 1996-2002), and recent-HAART (2003-2008) periods and total HAART era (July 1996-2008) were analysed and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 26 publications
5
47
1
Order By: Relevance
“…Mortality rates among HIVinfected patients in our institution mirror the rates in the pre-HAART era at other institutions. Independent predictors of mortality have been poor functional status, more than 1 year between HIV diagnosis and ICU admission, age, higher illness severity, low serum albumin, mechanical ventilation, and respiratory failure (17,24,25). This is likely due to a large number of HIV-infected individuals in the Atlanta area who lack access to medical care and health insurance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mortality rates among HIVinfected patients in our institution mirror the rates in the pre-HAART era at other institutions. Independent predictors of mortality have been poor functional status, more than 1 year between HIV diagnosis and ICU admission, age, higher illness severity, low serum albumin, mechanical ventilation, and respiratory failure (17,24,25). This is likely due to a large number of HIV-infected individuals in the Atlanta area who lack access to medical care and health insurance.…”
Section: Discussionmentioning
confidence: 97%
“…In the ICU, HAART has been associated with a number of predictors for decreased mortality, including higher CD4 count, lower viral load, lower Acute Physiology and Chronic Health Evaluation (APACHE) II score, and higher serum albumin (9). Although survival has improved for individuals living with HIV in the HAART era and some studies suggest that mortality rates are similar to non-HIV patients (10,16,17), optimal outcomes have not been achieved. Studies have shown that up to 50% of HIVinfected patients may not be on HAART at admission to the ICU (2,12).…”
mentioning
confidence: 96%
“…However, specific HIV characteristics (CD4 cell count, plasma HIV-RNA load, HIV-related diagnosis, or antiretroviral therapy) have not been clearly identified as predictors of ICU mortality [4,15,37,38,[49][50][51][52][54][55][56][57][58][59], although some reports have associated CD4…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In contrast, in developing settings those figures are lower, reflecting the high rates of late HIV presenters and opportunistic infections commonly seen in those places. 15 Modern ICU standards of care unrelated to HIV therapy (i.e.…”
Section: Impact Of Antiretroviral Therapymentioning
confidence: 75%